(untitled) (Revista Científica Compendium, 2019)
The aim of this research is to reconstruct the history of the Central-Western Cardiovascular Association of Venezuela (Ascardio) and the Regional Center for Cardiovascular Diseases of the State of Lara, in the context of the history of the Barquisimeto City-Region. The institutional antecedents and their insertion in the history of health institutions in Venezuela and in the Region in the historical social context of the last quarter of the 20th century are described. Additionally, their historical antecedents and the analysis of the reality of the institutions in Venezuela are presented.